2023
DOI: 10.1039/d3qo01149f
|View full text |Cite
|
Sign up to set email alerts
|

I2-DMSO mediated dual α,β-C(sp2)–H functionalization/bicyclization of o-hydroxyphenyl enaminones to construct C2,C3-disubstituted chromone derivatives: chromeno[2,3-b]pyrrol-4(1H)-ones

Shuang-Gui Lei,
You Zhou,
Li-Sheng Wang
et al.

Abstract: An unprecedented dual α,β-C(sp2)-H functionalization/bicyclization strategy of o-hydroxyphenyl enaminones for the preparation of chromeno[2,3-b]pyrrol-4(1H)-ones has been established. The multi-component cascade reaction achieves dual α,β-C(sp2)-H functionalization of o-hydroxyphenyl enaminones to construct...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To our delight, we successfully developed a new method for constructing chromeno[2,3- b ]pyrrole-4(1 H )-ones via I 2 –DMSO-mediated difunctionalization/cyclization of o -hydroxyphenyl enaminones (Scheme 47A). 57 A mechanism study showed that phenylketoaldehyde is nucleophilically attacked by o -hydroxyphenyl enaminone 47-1 to produce imine ion intermediate 47-2 , which is then converted to intermediate 47-3 by intramolecular cyclization. The chromone C2-substituted intermediate 47-4 is then immediately produced with the elimination of HNMe 2 , which can be oxidized to by-product 47-5 .…”
Section: Application Of the I2–dmso Reagent System To Aryl Methyl Ket...mentioning
confidence: 99%
“…To our delight, we successfully developed a new method for constructing chromeno[2,3- b ]pyrrole-4(1 H )-ones via I 2 –DMSO-mediated difunctionalization/cyclization of o -hydroxyphenyl enaminones (Scheme 47A). 57 A mechanism study showed that phenylketoaldehyde is nucleophilically attacked by o -hydroxyphenyl enaminone 47-1 to produce imine ion intermediate 47-2 , which is then converted to intermediate 47-3 by intramolecular cyclization. The chromone C2-substituted intermediate 47-4 is then immediately produced with the elimination of HNMe 2 , which can be oxidized to by-product 47-5 .…”
Section: Application Of the I2–dmso Reagent System To Aryl Methyl Ket...mentioning
confidence: 99%
“…Very recently, only one study from Wu's group disclosed a dual α,β-C(sp 2 )–H functionalization/bicyclization of o -HPEs for the construction of chromeno[2,3- b ]pyrrol-4(1 H )-ones through the above-mentioned traditional intramolecular chromone annulation strategy (Scheme 1c). 15 However, both the above-mentioned chromone construction strategies and the fused chromone construction strategy are traditional intramolecular chromone annulation processes from one molecule of o -HPE by first forming α-functionalized enaminone intermediates and then realizing chromone annulation with the hydroxyl group. To the best of our knowledge, a new intermolecular chromone annulation strategy of o -HPEs for the synthesis of (fused) chromone skeletons, especially using multiple molecules of o -HPEs to construct the chromone skeleton, still remains unexplored and very challenging (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…Enaminones have lately been known as utility and valuable reaction intermediates owing to the ambident nucleophilic and electrophilic characteristics of the enamine and enone groups, respectively, which were exploited by many synthetic chemists towards the synthesis of various biologically important heterocycles, such as some C3-functionalized chromones. 14–20 In particular, Yang and coworker reported the metal-free synthesis of difluoro/trifluoromethyl carbinol-containing chromones using o -hydroxyaryl enaminones as reaction substrates. 20 At the same time, photoredox catalysis and enzyme catalysis are also utilized to synthesize C3-functionalized chromones via the activation of the C(sp 3 )–H bond (Scheme 1).…”
mentioning
confidence: 99%